Pengaruh Edukasi Terhadap Pengetahuan Tentang Kekerasan Seksual Pada Anak Di SDN Sudiang Makassar - Febriani, Reski; Amelia, Kiki; Ratneni, Ratneni; Hasliani, Andi; Rahmawati, Rahmawati (Akademi Kebidanan Bunga Husada Samarinda, 2024)
About 20% of women and 5-10% of men in the world have experienced sexual violence in childhood. The purpose of this study was to determine the effect of education on knowledge about sexual violence in children at SDN Sudiang Makassar. This type of research is descriptive research with a Quasi experiment one groub pre and post test approach. the sample in this study were class V students as many as 36 respondents with total sampling technique. Data collection using questionnaire sheets. Data analysis using wilcoxon statistical test with a significant level of α = 0.05. Before giving education about sexual violence, the average knowledge of respondents on good knowledge was 8 students (22.2%), sufficient knowledge was 16 students (44.4%) and less knowledge was 12 students (33.3%) and after giving education about sexual violence in children, the average knowledge of children on good knowledge was 32 students (88.9%) and sufficient knowledge was 4 students (11.1%). The results of data analysis regarding the effect of providing education on sexual violence in children obtained a P-Value of 0.000 which means the Sig value <0.00 so that it can be interpreted that there is an effect of providing education on increasing students' knowledge about sexual violence in children. The conclusion in this study is that there is an effect of providing education on increasing female students' knowledge about sexual violence in children.